Development, validation, and results of a national endoscopy safety attitudes questionnaire (Endo-SAQ) - Ravindran, Srivathsan; Matharoo, Manmeet; Marshall, Sarah; Robinson, Emma; Bano, Madeline; Bassett, Paul; Coleman, Mark; Rutter, Matt; Ashrafian, Hutan; Darzi, Ara; Healey, Chris; Thomas-Gibson, Siwan (Endoscopy International Open, 2023)
Background and study aims Safety attitudes are linked to patient outcomes. The Joint Advisory Group on Gastrointestinal Endoscopy (JAG) identifies the need to improve our understanding of safety culture in endoscopy. We describe the development and validation of the Endo-SAQ (endoscopy safety attitudes questionnaire) and the results of a national survey of staff attitudes.Methods Questions from the original SAQ were adapted to reflect endoscopy-specific content. This was refined by an expert group, followed by a pilot study to assess acceptability. The refined Endo-SAQ (comprising 35 questions across six domains) was disseminated to endoscopy staff across the UK and Ireland. Outcomes were domain scores and the percentage of positive responses (score ≥75/100) per domain. Descriptive and comparative analyses were performed. Binary logistic regression identified staff and service factors associated with positive scores. Validity and reliability of Endo-SAQ were assessed through psychometric analysis.Results After expert review, four questions in the preliminary Endo-SAQ were adjusted. Sixty-one participants undertook the pilot study with good acceptability. A total of 453 participants completed the refined Endo-SAQ. There were positive responses in teamwork, safety climate, job satisfaction, and working conditions domains. Endoscopists had significantly more positive responses to stress recognition and working conditions than nursing staff. JAG accreditation was associated with positive scores in safety climate and job satisfaction domains. Endo-SAQ met thresholds of construct validity and reliability.Conclusions Endoscopy staff had largely positive safety attitudes scores but there were significant differences across domains and staff. There is evidence for the validity and reliability of Endo-SAQ. Endo-SAQ could complement current measures of patient safety in endoscopy and be used in evaluation and research.
Keywords: Quality and logistical aspects; Quality and logistical aspects; Performance and complications; Quality and logistical aspects; Training